Attitudes of employees towards affirmative action and job satisfaction in the South African Broadcasting Corporation ( SABC), Limpopo Province / - Maphoso, Lesiba Samuel Thitshere (University of Limpopo, 2014)
The purpose of this study was to investigate if there was any statistical significant difference in attitude towards Affirmative Action and job satisfaction of employees in the South African Broadcasting Corporation in Limpopo Province (SABC Limpopo Combo). The Attitude towards Affirmative Action Questionnaire (AAAQ) and the Job Satisfaction Questionnaire (JSQ) were distributed among employees/journalists (N=86) who were randomly selected. The results were analysed using the Chi-Square test and the t-test. The results revealed no statistical significant difference in attitudes towards Affirmative Action among employees or journalists and no significant relationship between attitudes towards Affirmative Action and job satisfaction. However, results revealed that senior employees/journalists were more satisfied than junior employees/journalists in (1) pay and benefits, and (2) job activities/work itself. Recommendations were made, which may be considered during the interpretation of organisational turnaround strategies and employment equity in workplaces or in the media.
Thesis (M.A. (Media Studies)) --University of Limpopo, 2014
Keywords: Affirmative action; Job satisfaction; South African Broadcasting Corporation; SABC Limpopo Combo; Radio journalists; Media; 331.133.; Affirmative action programs -- South Africa; Job satisfaction -- Measurement